Increasing Competitive Advantage through Implementation Green Human Resource Management (GHRM) Model at the Leading UMKM of Tasikmalaya City - Barlian, Barin; Karmila, Mila; Patimah, Titin; Maulana, Sesep; Restiani, Melpa; Rohman, Gifar Fathur; Kartiko, Alfi Rahadya (Journal of Business Management Education (JBME), 2024)
This study aims to determine the understanding of leading MSMEs in Tasikmalaya City regarding Green Human Resource Management (GHRM), analyze and determine the extent of the role of Green Human Resource Management (GHRM) in increasing Sustainable Business Performance or increasing the competitive advantage of Leading MSMEs in Tasikmalaya City. The research sample consisted of 39 leading MSMEs spread across 5 (five) sub-districts in Tasikmalaya City. The data analysis used in this study was descriptive analysis. The results of the study showed that only a few MSMEs already knew about the concept of GHRM but had not been able to apply it optimally to their businesses. The results of this study also produced a GHRM concept/model that can be applied to leading MSMEs in Tasikmalaya City which includesbackground, stimulus, implementation and expected output from the implementation of Green Human Resource Management. The background explains why Green Human Resource Management needs to be implemented, Stimulus is something that encourages subjects both organizationally and individually to implement/do something. Some determinants that are thought to encourage a company or individual employee to behave in an environmentally friendly manner are, environmental ethics awareness, organizational culture and organizational/leadership commitment. The concept is expected to increase the competitiveness of MSMEs and produce a better company work environment